Genomic evidence supporting the clonal expansion of extensively drug-resistant tuberculosis bacteria belonging to a rare proto-Beijing genotype. Issue 1 (1st January 2020) - Srilohasin, Prapaporn; Prammananan, Therdsak; Faksri, Kiatichai; Phelan, Jody E.; Suriyaphol, Prapat; Kamolwat, Phalin; Smithtikarn, Saijai; Disratthakit, Areeya; Regmi, Sanjib Mani; Leechawengwongs, Manoon; Twee-Hee Ong, Rick; Teo, Yik Ying; et al.
ABSTRACT: Tuberculosis disease (TB), caused by Mycobacterium tuberculosis, is a major public health issue in Thailand. The high prevalence of modern Beijing (Lineage 2.2.1) strains has been associated with multi- and extensively drug-resistant infections (MDR-, XDR-TB), complicating disease control. The impact of rarer proto-Beijing (L2.1) strains is less clear. In our study of thirty-seven L2.1 clinical isolates spanning thirteen years, we found a high prevalence of XDR-TB cases (32.4%). With ≤ 12 pairwise SNP distances, 43.2% of L2.1 patients belong to MDR-TB or XDR-TB transmission clusters suggesting a high level of clonal expansion across four Thai provinces. All XDR-TB (100%) were likely due to transmission rather than inadequate treatment. We found a 47 mutation signature and a partial deletion of the fadD14 gene in the circulating XDR-TB cluster, which can be used for surveillance of this rare and resilient M. tuberculosis strain-type that is causing increasing health burden. We also detected three novel deletion positions, a deletion of 1285 bp within desA3 (Rv3230c), large deletions in the plcB, plcA, and ppe38 gene which may play a role in the virulence, pathogenesis or evolution of the L2.1 strain-type.